IMPLEMENTATION OF IJARAH ACCOUNTING IN PT. BANK SYARIAH MANDIRI - Meita Putri; Imam Subaweh (Universitas Gunadarma, 2019)
The development of Islamic banking is fast and increased in the ability to survive in the economic crisis compared to conventional banks create public confidence. In addition to avoid interest, Islamic banking offers a wide range of financial products as well that can be enjoyed by customers. This study focuses on one of the Islamic banks' product namely ijarah. PT. Bank Syariah Mandiri is chosen to be the object of the study. The study investigated three aspects namely procedures, recording and reporting of ijarah transactions in PT. Bank Syariah Mandiri. Ijarah financing procedures in PT. Bank Syariah Mandiri had been properly operated by some prior analysis to the disbursement of funds from the bank. For the Ijarah transaction report, PT. Bank Syariah Mandiri has been noted several reports, for instance, the balance sheet, income statement, cash flow statement and reconciliation report income and profit-sharing statement. While for Ijarah transaction recorded in the financial statements are in line with SFAS Number107.